2019
DOI: 10.3389/fmicb.2019.02327
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Bacillus subtilis Lipopeptides to Two Venturia inaequalis Strains Possessing Different Tebuconazole Sensitivity

Abstract: Within the framework of biocontrol development, three natural substances produced by Bacillus subtilis, called lipopeptides, have been studied: fengycin (F), surfactin (S), and mycosubtilin (M). Their antifungal properties were tested in vitro, in liquid medium, on two strains of Venturia inaequalis, ascomycete fungi causing apple scab. These two strains were, respectively sensitive and less sensitive to tebuconazole, an active substance of the triazole family. These three molecules were tested on their own, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 69 publications
6
54
0
1
Order By: Relevance
“…Although the inhibition of fungal pathogens is beneficial to a developing crop, the potential inhibition of spore germination and hyphal development of AM fungi is a negative secondary impact. The decline in mean arbuscule count ( Figure 1 ) lends further support to a fungal inhibitory mechanism due to B. subtilis , corroborating [ 62 ] and [ 71 ]. The method of soil management and the use of tillage does not appear to influence the magnitude of the negative effect of B. subtilis on AM fungi and soil glomalin concentration ( Figure 7 and Figure 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…Although the inhibition of fungal pathogens is beneficial to a developing crop, the potential inhibition of spore germination and hyphal development of AM fungi is a negative secondary impact. The decline in mean arbuscule count ( Figure 1 ) lends further support to a fungal inhibitory mechanism due to B. subtilis , corroborating [ 62 ] and [ 71 ]. The method of soil management and the use of tillage does not appear to influence the magnitude of the negative effect of B. subtilis on AM fungi and soil glomalin concentration ( Figure 7 and Figure 8 ).…”
Section: Discussionsupporting
confidence: 71%
“…Mycosubtilin belongs to the iturin family, and these biosurfactants are known to increase membrane cell permeability due to the formation of ion-conducting pores, with their characteristics depending on lipid membrane composition and the peptide cycle structure. It has been suggested that ionic pores are attributed to lipopeptide or lipopeptide/phospholipid complex aggregates in the phospholipid membrane ( Maget-Dana and Peypoux, 1994 ; Desmyttere et al, 2019 ). A study investigating in vitro susceptibilities of the abovementioned yeasts to purified anteiso-C17 mycosybtilin homologue showed MIC ranging between 2 and 150 mg/L ( Fickers et al, 2009 ), which are within the range of MICs observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Lipopeptides produced by genus Bacillus are mainly classified into three families depending on their amino-acid sequences: surfactin, iturin, and fengycin. These families share a cyclic β-amino or β-hydroxy fatty acid linked to a cyclic heptapeptide (3,9).…”
mentioning
confidence: 99%